The Promotion Strategy for Virgin Coconut Oil Products in The Pangsan Ayu Group, Petang District, Badung District - Upadani, I Gusti Ayu Widari; Triandini, Evi; Srinadi, Ni Luh Putri; Krisnawan, Gusti Ngurah Aditya; Saputra, Kadek Surya (Universitas Mercu Buana, 2025)
Objectives: Virgin Coconut Oil (VCO) is oil obtained from the processing of coconuts, this VCO has many benefits, especially for health and beauty. However, this product still faces obstacles in the marketing process. Digital marketing is one solution that can be offered to the Pangsan Ayu group. The purpose of this research is to determine the marketing system used and to determine the appropriate marketing method used by the Pangsan Ayu group.Methodology The research was conducted using a survey method through the use of questionnaires and in-depth interviews. The quantitative and qualitative data obtained were analyzed using statistical analysis with SPSS version 25 application. Primary data was obtained from questionnaires given to 96 respondents, consisting of 90 consumers, 4 producers (Pangsan Ayu group) and 2 representatives of the Pangsan Village government.Finding: The research results show that: The group has carried out the planning stage before carrying out the production process 83.3%. Apart from that, the group has also received training (33.3%) and is skilled in processing VCO (33.3%) and the group has divided work tasks (66.7%) in carrying out production.Conclusion: All consumers, 100% of the 90 people who were respondents, said they had used Pangsan Ayu VCO, had purchased it by order, so they recommended using VCO. Most of the 66.7% VCO oil is sold at IDR 35,000, this price is considered cheap at 34.4% and some say the price is moderate at 61.1%. VCO quality is good at 44.4%, attractive at 44.4% and the information conveyed on the packaging label is complete. Most of Pangsan Ayu's VCO products are 51.1% for beauty and 44.4% for health.